Examination of Hysterosalpingography in Patients With Suspected Infertility at The Radiology Department of Dr.R. Soetrasno Rembang Hospital - Retno Wati; Siti Masrochah (Universitas 'Aisyiyah Yogyakarta, 2021)
Hysterosalpingography (HSG) is the most commonly used imaging diagnostic to determine the tubal patency in patient with indications of infertility. The technique used in the HSG procedure is different in some studies. The aim of this study was to determine the technique of hysterosalpingography (HSG) examination with patients suspected of infertility in dr.R. Soetrasno Rembang hospital. The method was a case study approach. Results showed HSG examination using plain photo Anteroposterior (AP) projection, AP projection with 3 cc contrast media and 7 cc contrast media, then post evacuation. The AP projection already revealed uterus, fallopian tubes, spill on the peritoneum, reduce radiation dose, and the pain of patients. They used 3 cc and 7 cc of contrast media because the examination did not use fluoroscopy. The 3 cc of contrast media views the uterus only then 7 cc view the fallopian tube and its spill. HSG plays a crucial role to determine the cause of infertility, especially to evaluate the morphology and patency of the fallopian tubes in women so the radiology team should become familiar with examination techniques used, give the patient education to avoid movement, and hold their body motionless also taking a mild pain reliever before the HSG examination.